Investigations into ventral prefrontal cortex using mediation models. Issue 4 (17th August 2019) - Hu, Kesong
Abstract: The ventral prefrontal cortex (vPFC) is a major focus of investigation in neuroscience, particularly in the studies of emotion and emotion‐cognition integration. A crucial question concerning the regulatory function of vPFC is how it is recruited, especially how the function maps onto the structure and determines appropriate behavior. In social exclusion studies, mediation model analyses suggest that vPFC regulates distress by disrupting anterior cingulate cortex (ACC) activities, whereas I recently report (Hu, 2018; Neuropsychologia) that ventral medial prefrontal cortex appears to defend the organism from acute stress by activating ACC. In this review, I synthesize and highlight functional imaging research with mediation analysis that over the past decades has begun to offer new insights into the brain mechanisms underlying vPFC. Toward this end, the first section of the paper outlines a model of the processes and neural systems involved in the interaction of emotion and cognition. The second and third sections survey recent research on emotional regulation with negative and positive pathways, respectively, emanating from vPFC. The fourth section summarizes the current dynamic network findings. Functional mediation analysis helps to identify signals within vPFC and others that are common and/or specific to particular information processing. Finally, I provide a personal perspective of the adoption of mediation model analysis in the investigations into vPFC.